High-iron low-silicon oxidized pellet and preparation method thereof

By replacing bentonite with slurry-based binder, high-iron low-silicon oxidation pellets are prepared, which solves the problems of poor dispersion and insufficient strength of traditional binders, improves the physical and metallurgical properties of the pellets, and improves their blast furnace smelting. performance.

CN119506566APending Publication Date: 2025-02-25PANZHIHUA MINING FRIENDS NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411540622.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the large residual amount of bentonite leads to a decrease in the grade of the pellet ore, and the organic binder and composite binder have problems such as poor dispersion, low thermal strength of raw balls, poor strength of preheated pellets, and easy to produce powder.

Method used

Use slurry-based binder to replace traditional bentonite. By spraying slurry-based binder into vanadium titanium magnet concentrate, it is strongly rolled and mixed with strong mixer to form a dense and uniform mixture, and then it is made of a disk. The ball is made by a machine and dried, preheated, calcined and cooled.

Benefits of technology

Improve the physical properties of the pellets, such as compressive strength and wear resistance, and improve metallurgical properties, such as reducing and softening temperature, solve problems such as poor dispersion and low thermal strength, and improve the pellets in blast furnace smelting. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506566A_ABST
    Figure CN119506566A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of iron and steel smelting, in particular to a high-iron low-silicon oxidized pellet and a preparation method thereof.The preparation method comprises the following steps that a slurry-based binder is sprayed into vanadium-titanium magnetite concentrate, the mixture is strongly ground and then fed into a strong mixing machine to be fully and evenly scattered, and a mixture is obtained; pelletizing the mixed material; sequentially drying, preheating, roasting and cooling the made green pellets to obtain oxidized pellets; wherein the usage amount of the slurry-based binder is 1%-2% of the mass of the vanadium-titanium magnetite concentrate. The slurry-based binder is adopted to replace bentonite to prepare the high-iron low-silicon oxidized pellets, so that the physical properties, such as compressive strength and wear resistance, of the pellets are improved, the metallurgical properties, such as reducibility and softening temperature, of the pellets are improved, and the performance of the pellets in blast furnace smelting is improved. The problems that in the actual production of oxidized pellets, a high-viscosity fluid binder is small in dosage, non-uniform in addition, poor in dispersity, difficult to control in the pelletizing process, poor in strength of preheated pellets and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel smelting, and in particular to a high-iron and low-silicon oxide pellet and a preparation method thereof. Background Art

[0002] Bentonite is the most widely used pelletizing binder in pellet production, accounting for more than 90%. Its main component is aluminosilicate. The amount of bentonite used in domestic pelletizing plants is generally around 2%, and some manufacturers use less than 2%. Bentonite has a large residual amount during the pellet roasting process, which reduces the iron grade of the pellet ore. When its usage increases by 1%, the iron grade of the pellet ore decreases by 0.6%-0.7%, and the SiO2 content increases by 0.4%-0.5%.

[0003] In addition, organic binders can also be used to prepare oxidized pellets. Although the amount of organic binder used is 1 / 5-1 / 10 of that of bentonite, the hot strength of raw balls made with organic binders is low, the strength of preheated pellets is poor, and powder is easily generated. It cannot meet the production process requirements of domestic vertical furnaces and chain grate machines-rotary kilns, and it is expensive, with the cost of use exceeding twice that of bentonite.

[0004] There are two main types of organic-inorganic composite binders currently used. One is a composite binder based on inorganic components, organic modified bentonite, which reduces the amount of bentonite (1%-1.5%) while improving the strength of green balls. However, the introduction of organic matter has a great impact on the thermal properties of green balls, and has not fundamentally solved the problem of bentonite reducing iron grade. In addition, the price of the binder is significantly higher than that of bentonite. The other is a composite binder based on organic components, F binder, which has been successfully applied to the production of direct reduction pellets in coal-based rotary kilns in my country, with a ratio of 1.5%-2%; however, when F binder is used to prepare oxidized pellets, it has poor dispersibility in iron concentrate, and if the amount is too low, the fluctuation in the pelletizing process is large. If the amount added is too large, the combustion and decomposition of organic matter in the thermal process hinders the oxidation of iron ore and the consolidation process of pellets, forming pellets with a double-layer structure, and the compressive strength of the pellets is slightly reduced.

[0005] In view of this, the present invention proposes a production method for producing high-iron and low-silicon oxide pellets by using a slurry-based binder instead of traditional bentonite as a binder. Summary of the invention

[0006] The purpose of the present invention is to provide a high-iron and low-silicon oxide pellet and a preparation method thereof, which solves the problems of poor dispersibility of organic binders and composite binders, low hot strength of green pellets, poor strength of preheated pellets, and easy generation of powder.

[0007] In a first aspect, the present invention provides a method for preparing high-iron and low-silicon oxide pellets, comprising the following steps:

[0008] S1. Spray a slurry-based binder into the vanadium-titanium magnetite concentrate, vigorously roll the mixture, and then send it into a strong mixer to fully disperse it to obtain a mixture;

[0009] S2. Use a disc ball making machine to make balls for the mixed material. During the ball making process, the quality of the raw balls is controlled by adjusting the inclination angle, height, rotation speed and feed amount of the disc ball making machine;

[0010] S3, drying, preheating, roasting and cooling the prepared green pellets in sequence to obtain oxidized pellets;

[0011] The usage of the slurry-based binder is 1%-2% of the mass of the vanadium-titanium magnetite concentrate.

[0012] The present invention adopts a slurry-based binder to replace bentonite to prepare high-iron and low-silicon oxide pellets. The use of the slurry-based binder helps to adjust the microstructure inside the pellets to make them more dense and uniform, which not only improves the physical properties of the pellets, such as compressive strength and wear resistance, but also helps to improve the metallurgical properties of the pellets, such as reducibility and softening temperature, thereby improving their performance in blast furnace smelting. The present invention solves the problems of poor dispersibility of organic binders and composite binders, low hot strength of green pellets, poor strength of preheated pellets, and easy generation of powder.

[0013] The slurry-based binder used in the present invention is preferably a slurry obtained by oxidation fermentation and slurry modulation of low-rank coal. During the oxidation fermentation process, some chemical bonds in the low-rank coal are broken, forming more oxygen-containing functional groups, such as hydroxyl, carboxyl, etc. These functional groups have strong polarity and hydrophilicity, which can increase the wettability and adhesion of the coal surface; in addition, oxidation fermentation can also promote the generation of humic acid in coal. Humic acid is a natural organic polymer compound with good adhesion and dispersibility, and can be used as an effective binder; during the oxidation fermentation process, the porosity and particles of coal may become smaller, so that the contact between coal particles is closer, and it is easier to form a uniform slurry, which is not only conducive to the formation of adhesion, but also can be filled into the gaps between coal particles during the bonding process to enhance the bonding effect; during the oxidation fermentation process, microorganisms will also secrete various metabolites, such as enzymes, polysaccharides, etc. These metabolites have a certain bonding effect and can enhance the bonding between coal particles; in addition, some cell wall components of microorganisms may also be released during the fermentation process and become part of the slurry, which has a positive effect on the bonding performance. Therefore, the slurry-based adhesive used in the present invention has the advantages of high viscosity, good bonding performance, and the effective components can form a stable dispersed phase in the slurry.

[0014] As a preferred embodiment of the present technical solution, in step S1, when the slurry-based binder is sprayed into the vanadium-titanium magnetite concentrate, the vanadium-titanium magnetite concentrate is first formed into a uniform material curtain by a roller screen device, and then the slurry-based binder is sprayed into the vanadium-titanium magnetite concentrate material curtain at a certain angle by means of pressurized atomization of a nozzle.

[0015] The present invention forms a uniform columnar material curtain with vanadium-titanium magnetite concentrate by setting a roller screen, and uses a fan-shaped nozzle to spray the slurry-based binder into the vanadium-titanium magnetite concentrate material curtain at a certain angle, thereby solving the problem of substantially uniform addition of slurry-based colloid and iron concentrate.

[0016] Specifically, the moisture content of the vanadium-titanium magnetite concentrate raw material used in the present invention is 7wt%-10wt%. After the slurry-based binder is added, the moisture content of the mixture is maintained at 8wt%-10wt%, and preferably 9wt%. The actual solid amount of the slurry-based binder added to the vanadium-titanium magnetite concentrate is only 0.2%-0.4%, and the rest is water, which greatly reduces the amount of adhesive used.

[0017] As a preferred embodiment of the present technical solution, in step S1, the slurry-based binder is chemically adsorbed on the surface of the new particles of the vanadium-titanium magnetite concentrate under strong rolling by means of high-pressure roller milling, so as to give full play to the role of organic matter and mineral particles; after high-pressure roller milling, strong mixing is added to further break up and mix the agglomerated materials formed after high-pressure roller milling, thereby improving the dispersion effect. Specifically, during the rolling, the gap of the high-pressure roller mill is controlled to be 19-20mm, the roller pressure is 7-9MPa, and preferably 8MPa, that is, by controlling the roller spacing and pressure, the slurry-based binder can be fully combined with the vanadium-titanium magnetite concentrate.

[0018] In the traditional pelletizing production method, the binder is usually added after the high-pressure roller mill. This invention adjusts the adding position to before the high-pressure roller mill, solving a series of problems such as the binder effect and sufficient mixing.

[0019] As a preferred embodiment of the present technical solution, in step S2, during the ball making, the inclination angle of the disc ball making machine is controlled to be 45-55o, and preferably 49o, the disc diameter of the disc ball making machine is 5-7m, and preferably 6m, the height of the lowest point of the disc surface is 1-2m, and preferably 1.6m, the rotation speed of the disc ball making machine is 5-10rpm / min, and preferably 8rpm / min, the feed amount of the disc ball making machine is 40-50 tons / h, and the disc ball making machine increases its rotation speed, which increases the ball output speed while ensuring the density of the raw balls.

[0020] The slurry-based binder ball-forming process of the present invention is different from that of traditional bentonite. During the ball-forming process, the moisture of the binder in the raw ball migrates quickly, the ball-forming speed is fast, and by controlling a series of ball-forming parameters, it is easy to produce qualified raw balls and the ball-forming process is stable and controllable.

[0021] As a preferred embodiment of the present technical solution, in step S2, during the ball making, the particle size range of the green balls is controlled to be 8-16 mm, the falling strength of the green balls is not less than 3 times / 0.5 m / piece, and the compressive strength of the green balls is not less than 10 N / piece, so as to prevent the green balls from breaking during the transportation process before entering the chain grate machine for drying.

[0022] As a preferred embodiment of the present technical solution, during the drying, the balls are first dried at 100-300°C for 1-5 minutes in a low wind speed section of 1.0-1.4 m / s, and then dried at 300-500°C for 9-10 minutes in an exhaust drying section; during the preheating, the temperature is controlled at 900-920°C for 12-14 minutes. Prolonging the drying and preheating time appropriately can ensure the strength of the preheated balls.

[0023] When the preheating temperature is low, the magnetite is not fully oxidized and the pellet strength is low; the oxidation of the magnetite pellet is carried out in layers from the surface to the center of the ball. Therefore, when the preheating temperature is too high, a denser Fe2O3 shell will be formed on the outer layer of the pellet, which will hinder the diffusion of external oxygen into the interior of the pellet, thereby affecting the strength of the preheated pellet.

[0024] As a preferred embodiment of the present technical solution, during the calcination, the temperature is controlled to be 1220-1260°C and the time is 32-39 minutes.

[0025] The compressive strength of the pellets after calcination increases with the increase of calcination temperature, and the compressive strength of the calcined pellets increases first and then decreases with the extension of calcination time. For example, when the calcination temperature rises to 1250℃, the compressive strength of the pellets after calcination is greater than 2000N / P, which meets the production requirements.

[0026] By adjusting the thermal parameters of the chain grate machine, rotary kiln, etc., the adverse effects of adding organic matter during the preheating process, such as the generation of pores and heat, which are different from traditional bentonite production, were solved.

[0027] As a preferred embodiment of the present technical solution, during the cooling, the cooling wind speed of the ring cooler is controlled to be 2.2-2.4 m / s, and the cooling and discharging time is 40-50 min.

[0028] In the second aspect, the present invention also discloses high-iron and low-silicon oxide pellets prepared using the above-mentioned preparation method, which should also fall within the protection scope of the present invention.

[0029] The method for preparing high-iron and low-silicon oxide pellets of the present invention has at least the following beneficial effects:

[0030] 1. The present invention adopts a slurry-based binder to replace bentonite to prepare high-iron and low-silicon oxide pellets. The use of a slurry-based binder helps to adjust the microstructure inside the pellets, making them more dense and uniform, which not only improves the physical properties of the pellets, such as compressive strength and wear resistance, but also helps to improve the metallurgical properties of the pellets, such as reducibility and softening temperature, thereby improving their performance in blast furnace smelting. It solves the problems of poor dispersibility of organic binders and composite binders, low hot strength of green balls, poor strength of preheated pellets, and easy generation of powder;

[0031] 2. In the preparation method of high-iron and low-silicon oxidized pellets of the present invention, first, a slurry-based binder is sprayed into the vanadium-titanium magnetite concentrate, and the mixture is vigorously rolled and then sent to a strong mixer to be fully dispersed and evenly dispersed, thereby obtaining a mixture. This mixing method can not only improve the dispersibility of the slurry-based binder in the vanadium-titanium magnetite concentrate, but also significantly improve the adhesion of the mixture, so that more solid pellets can be formed in the subsequent pelletizing process; at the same time, by accurately controlling the amount of the slurry-based binder, the introduction of excessive foreign impurities such as silicon elements is avoided, the iron grade of the oxidized pellet ore is significantly improved, the silicon content is reduced, the metallurgical properties of the oxidized pellets are improved, the product quality is improved, and the production cost is reduced; then, a disc pelletizer is used to pelletize the mixture. During the pelletizing process, the quality of the raw balls can be controlled by adjusting the inclination angle, height, rotation speed and feed amount of the disc pelletizer; finally, the prepared raw balls are dried, preheated, roasted and cooled in sequence to prepare oxidized pellets. The method of the present invention shows remarkable beneficial effects in improving pellet quality, reducing silicon content, improving production efficiency and environmental protection benefits, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 The present invention is a flow chart of the method for preparing high-iron and low-silicon oxide pellets. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] S1. Using vanadium-titanium magnetite with a raw material moisture content of 8.0wt% as raw material to produce oxidation pellets, forming a uniform material curtain of vanadium-titanium magnetite concentrate through a roller screen device, and then spraying a slurry-based binder accounting for 1.5wt% of the mass of vanadium-titanium magnetite into the vanadium-titanium magnetite concentrate material curtain at a certain angle through a fan-shaped nozzle pressurized atomization method, and maintaining the moisture content of the pellets at 9wt%, and then strongly rolling the mixture and sending it to a strong mixer to fully disperse it to obtain a mixed material, wherein during rolling, the gap of the high-pressure roller mill is controlled to be 19mm, and the roller pressure is 8MPa;

[0039] S2. Use a disc ball making machine to make balls for the mixed material. During the ball making process, the inclination angle of the disc ball making machine is controlled to be 49o, the disc diameter of the disc ball making machine is 6m, the height of the lowest point of the disc surface is 1.6m, the speed of the disc ball making machine is 8rpm / min, the feed rate of the disc ball making machine is 40-50 tons / h, the particle size range of the obtained raw balls is 8-16mm, the falling strength of the raw balls is 4 times / 0.5m / piece, and the compressive strength of the raw balls is 13.6N / piece;

[0040] S3. Send the prepared green balls into the chain grate for drying and preheating. First, dry them at 300℃ for 2min in the low wind speed section of 1.0-1.4m / s, then transfer to the exhaust drying section to dry at 500℃ for 9min, and further preheat at 920℃ for 12min. The preheated balls enter the rotary kiln for roasting. The roasting temperature is 1220℃-1260℃ and maintained for 35min. The roasted balls enter the ring cooler for cooling. The blast cooling wind speed is 2.2-2.4m / s. The whole process of cooling and discharging is 40-50min to obtain oxidized balls.

[0041] The average compressive strength of the oxidized pellets prepared in this embodiment is 2097N / piece, the drum strength of the oxidized pellets is 93.8wt%, the content of TFe in the oxidized pellets is 55.35wt%, the content of FeO is 2.85wt%, and the content of SiO2 is 3.8wt%.

[0042] Example 2

[0043] S1. Using vanadium-titanium magnetite with a moisture content of 8.0wt% as raw material to produce oxidation pellets, forming a uniform material curtain through a roller screen device, and then spraying a slurry-based binder accounting for 1.5wt% of the mass of the vanadium-titanium magnetite at a certain angle into the vanadium-titanium magnetite concentrate material curtain through a fan-shaped nozzle pressurized atomization method, and maintaining the moisture content of the pellets at 9wt%. After strongly rolling the mixture, it is sent to a strong mixer to be fully dispersed and evenly dispersed to obtain a mixture, wherein during rolling, the gap of the high-pressure roller mill is controlled to be 20mm and the roller pressure is 9MPa;

[0044] S2. Use a disc ball making machine to make balls for the mixed material. During the ball making process, the inclination angle of the disc ball making machine is controlled to be 49o, the disc diameter of the disc ball making machine is 6m, the height of the lowest point of the disc surface is 1.6m, the speed of the disc ball making machine is 10rpm / min, the feed rate of the disc ball making machine is 40-50 tons / h, the particle size range of the obtained raw balls is 8-16mm, the falling strength of the raw balls is 4 times / 0.5m / piece, and the compressive strength of the raw balls is 14N / piece;

[0045] S3. Send the prepared green balls into the chain grate for drying and preheating. First, dry them at 200℃ for 3min in the low wind speed section of 1.0-1.4m / s, then transfer to the exhaust drying section and dry them at 400℃ for 9-10min, and further preheat them at 900℃ for 12-14min. The preheated balls enter the rotary kiln for roasting. The roasting temperature is 1220℃-1260℃ and maintained for 35min. The roasted balls enter the ring cooler for cooling. The blast cooling wind speed is 2.2-2.4m / s. The whole process of cooling and discharging is 40-50min to obtain oxidized balls.

[0046] The average compressive strength of the oxidized pellets prepared in this embodiment is 2098N / piece, the drum strength of the oxidized pellets is 93.9wt%, the content of TFe in the oxidized pellets is 55.45wt%, the content of FeO is 2.85wt%, and the content of SiO2 is 3.7wt%.

[0047] Example 3

[0048] S1. Using vanadium-titanium magnetite with a moisture content of 8.0wt% as raw material to produce oxidation pellets, forming a uniform material curtain through a roller screen device, and then spraying a slurry-based binder accounting for 1.5wt% of the mass of the vanadium-titanium magnetite at a certain angle into the vanadium-titanium magnetite concentrate material curtain through a fan-shaped nozzle pressurized atomization method, and maintaining the moisture content of the pellets at 9wt%. After strongly rolling the mixture, it is sent to a strong mixer to be fully dispersed and evenly dispersed to obtain a mixture, wherein during rolling, the gap of the high-pressure roller mill is controlled to be 20mm and the roller pressure is 7MPa;

[0049] S2. Use a disc ball making machine to make balls for the mixed material. During the ball making process, the inclination angle of the disc ball making machine is controlled to be 49o, the disc diameter of the disc ball making machine is 6m, the height of the lowest point of the disc surface is 1.5m, the speed of the disc ball making machine is 8rpm / min, the feed rate of the disc ball making machine is 40-50 tons / h, the particle size range of the obtained raw balls is 8-16mm, the falling strength of the raw balls is 4 times / 0.5m / piece, and the compressive strength of the raw balls is 13.2N / piece;

[0050] S3. Send the prepared green balls into the chain grate for drying and preheating. First, dry them at 200℃ for 1-5min in the low wind speed section of 1.0-1.4m / s, then transfer to the exhaust drying section to dry at 350℃ for 10min, and further preheat at 920℃ for 12min. The preheated balls enter the rotary kiln for roasting. The roasting temperature is 1220℃-1260℃ and maintained for 38min. The roasted balls enter the ring cooler for cooling. The blast cooling wind speed is 2.2-2.4m / s. The whole process of cooling and discharging is 40-50min to obtain oxidized balls.

[0051] The average compressive strength of the oxidized pellets prepared in this embodiment is 2095N / piece, the drum strength of the oxidized pellets is 93.8wt%, the content of TFe in the oxidized pellets is 55.40wt%, the content of FeO is 2.80wt%, and the content of SiO2 is 3.7wt%.

[0052] Comparison example

[0053] This control example is basically the same as Example 1, except that: this control example uses bentonite accounting for 2 wt% of the mass of vanadium-titanium magnetite to replace the slurry-based binder in Example 1.

[0054] The particle size range of the green balls obtained in this control example is 8-16 mm, the drop strength of the green balls is 3.8 times / 0.5 m / piece, and the compressive strength of the green balls is 12.6 N / piece.

[0055] The average compressive strength of the oxidized pellets prepared in this comparative example is 2045N / piece, the drum strength of the oxidized pellets is 93.2wt%, the TFe content in the oxidized pellets is 54.45wt%, the Fe content is 3.24wt%, and the SiO2 content is 4.7wt%.

[0056] Figure 1 The present invention is a flow chart of the method for preparing high-iron and low-silicon oxide pellets.

[0057] Table 1 Performance of the oxidized pellets obtained in Examples 1-3 and Comparative Examples

[0058]

[0059] It can be seen from Table 1 that, under the condition of meeting the requirement of green ball drop strength higher than 3.0 times / (0.5m), the oxidized pellets produced by using 1.5wt% slurry-based binder are superior in quality to the oxidized pellets produced by using conventional bentonite as binder. The TFe content of the finished oxidized pellets is increased by 0.9 percentage points, and the SiO2 content is decreased by 0.9 percentage points.

[0060] In summary, the present invention adopts a slurry-based binder to replace bentonite to prepare high-iron and low-silicon oxide pellets, which not only improves the physical properties of the pellets, such as compressive strength and wear resistance, but also helps to improve the metallurgical properties of the pellets, such as reducibility and softening temperature, thereby improving its performance in blast furnace smelting. It solves the problems of poor dispersibility of organic binders and composite binders, low hot strength of green balls, poor strength of preheated pellets, and easy generation of powder.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing high iron and low silicon oxide pellets, characterized in that: The following steps are involved: S1. Spray a slurry-based binder into the vanadium-titanium magnetite concentrate, vigorously roll the mixture, and then send it into a strong mixer to fully disperse it to obtain a mixture; S2. Use a disc ball making machine to make balls for the mixed material. During the ball making process, the quality of the raw balls is controlled by adjusting the inclination angle, height, rotation speed and feed amount of the disc ball making machine; S3, drying, preheating, roasting and cooling the prepared green pellets in sequence to obtain oxidized pellets; The usage of the slurry-based binder is 1%-2% of the mass of the vanadium-titanium magnetite concentrate.

2. The preparation method according to claim 1, characterized in that: In step S1, when the slurry-based binder is sprayed into the vanadium-titanium magnetite concentrate, the vanadium-titanium magnetite concentrate is first formed into a uniform material curtain by a roller screen device, and then the slurry-based binder is sprayed into the vanadium-titanium magnetite concentrate material curtain by a nozzle pressurized atomization method.

3. The preparation method according to claim 1, characterized in that: In step S1, during the rolling, the gap of the high pressure roller mill is controlled to be 19-20 mm, and the roller pressure is controlled to be 7-9 MPa.

4. The preparation method according to claim 1, characterized in that: In step S2, during the ball making process, the inclination angle of the disc ball making machine is controlled to be 45-55°, the disc diameter of the disc ball making machine is 5-7m, the height of the lowest point of the disc surface is 1-2m, the rotation speed of the disc ball making machine is 5-10rpm / min, and the feed rate of the disc ball making machine is 40-50 tons / h.

5. The preparation method according to claim 1, characterized in that: In step S2, during the ball making, the particle size range of the green balls is controlled to be 8-16 mm, the falling strength of the green balls is not less than 3 times / 0.5 m / piece, and the compressive strength of the green balls is not less than 10 N / piece.

6. The preparation method according to claim 1, characterized in that: During the drying, the material is first dried at 100-300° C. for 1-5 minutes in a low wind speed section of 1.0-1.4 m / s, and then dried at 300-500° C. for 9-10 minutes in an exhaust drying section.

7. The preparation method according to claim 1, characterized in that: During the preheating, the temperature is controlled to be 900-920° C. and the time is 12-14 minutes.

8. The preparation method according to claim 1, characterized in that: During the calcination, the temperature is controlled to be 1220-1260° C. and the calcination time is 32-39 minutes.

9. The preparation method according to claim 1, characterized in that: During the cooling, the cooling wind speed of the ring cooler is controlled to be 2.2-2.4 m / s, and the cooling and discharging time is 40-50 min.

10. A high iron and low silicon oxide pellet, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.